Stacking order effects on the energetics and electronic properties of n-doped graphene/h-BN van der Waals heterostructures on SiC(0001) - Deus, Dominike P. de Andrade; Lopes, João Marcelo J.; Miwa, Roberto H. (Carbon (New York), 2023)
Heterostructures based on the stacking of two-dimensional materials with different electronic properties have been the subject of several studies addressing the development of novel devices with multiple functionalities. Graphene (G)/hexagonal boron nitride (h-BN) van der Waals (vdW) systems have been extensively investigated, including studies on the large-scale synthesis of h-BN on graphene/SiC(0001) substrate. This work is a theoretical study using first-principles calculations of bilayer (G/h-BN) and trilayer (G/h-BN/G) heterostructures on SiC(0001) covered by a carbon buffer layer (SiC). The results show an energetic preference for h-BN encapsulation below a single layer of graphene on SiC, viz.: G/h-BN/SiC in the case of bilayer systems and G/h-BN/G/SiC in the case of trilayer systems. Indeed, the electronic structure calculations reveal the preservation of graphene linear energy band dispersion in the bilayer systems. The trilayer systems’ electronic structure depends on the stacking order, with the emergence of parabolic bands in energetically less stable systems. Structural characterizations of these bilayers and trilayers on SiC were carried out based on simulations of C-1s core-level-shift (CLS) and carbon K-edge X-ray absorption near edge spectroscopy (XANES) with the goal of assisting future experimental spectroscopy in these graphene/h-BN vdW systems. [Display omitted]